Preparation and properties of monomethoxyl polyethylene glycol grafted O-carboxymethyl chitosan for edible, fresh-keeping packaging materials. (September 2022) - Yang, Bing; Yin, Shengnan; Bian, Xiaofang; Liu, Changlin; Liu, Xinhong; Yan, Yongli; Zhang, Chunxia; Zhang, Hui; Hou, Zhaosheng
Abstract: The main target of the current exploration is to represent a novel type of edible biomaterial composed of monomethoxyl polyethylene glycol-modified O-carboxymethyl chitosan (MPEG-O-CMC) for fresh-keeping food packaging materials. MPEG-O-CMCs were prepared by a facile method that consists of three steps: the C6 -hydroxyl group of chitin (CH) was first substituted by chloroacetic acid; O-carboxymethyl chitosan (O-CMC) was subsequently obtained via a deacetylation reaction; and finally, the NH2 groups of O-CMC were reacted with isocyanate-terminated methoxypolyethylene glycol (MPEG-NCO) to yield MPEG-O-CMC. The chemical structures of O-CMC, MPEG-NCO, and MPEG-O-CMC were scrutinized through nuclear magnetic resonance spectroscopy (NMR) and Fourier transform–infrared spectroscopy (FT-IR), and the influences of the MPEG content on the physicochemical features of the solution-cast MPEG-O-CMC films was extensively researched. The results showed that the introduction of polyethylene glycol (PEG) could ameliorate the hydrophilicity, thermal stability, flexibility, and tensile features of the film. When the grafting degree of MPEG was approximately 25% (the MPEG content in MPEG-O-CMC was 18.5  wt %), the film possessed a lower T g of −30 °C and higher tensile features (strain at break: 221%; ultimate stress: 4.4 MPa). The water vapor transmission rates (WVTR) of the MPEG-O-CMC films was evaluated by osmosis tests at different humidity, and the results showed that films possessed good WVTR of 25–200 g·mm/(m 2 ∙24 h) at 50% humidity. The WVTR decreased gradually with the increase of MPEG content in the material, which was mainly attributed to the flexible MPEG segments acting as a plasticizer and reducing the dimension of the transient interspaces. Furthermore, the preliminary evaluation of bacteriostatic activity indicated that the films possess a certain bacteriostatic activity against Escherichia coli . Due to its good tensile properties, acceptable WVTR and potential bacteriostatic activity, this nontoxic and even edible biomaterials hold significant promise for application in fresh-keeping food packing materials. Highlights: The MPEG-grafted O-CMCs are degradable and even edible. The MPEG-O-CMC films possess good tensile properties and satisfied water permeability. The MPEG-O-CMC provides films with additional bacteriostatic ability.